Analisis Perbedaan Hasil Produksi ASI dan Status Gizi Ibu Menyusui sebelum dan setelah Konsumsi Food Bar Tepung Daun Katuk (Sauropus Androgynus) dan Daun Torbangun (Coleus Amboinicus) di Kelurahan Limo, Depok: Analysis of Differences in Breast Milk Production and Nutritional Status of Breastfeeding Mothers in Limo Subdistrict, Depok Before and After Consuming Food Bars Made from Katuk (Sauropus Androgynus) and Torbangun (Coleus Amboinicus) Leaves - Karlina, Dinda; Nasrullah, Nanang; Sufyan, Dian Luthfiana (Universitas Airlangga, 2025)
Background: Some mothers perceive that their breast milk production is insufficient, which hinders them from breastfeeding their infants. Based on data from the Indonesian Ministry of Health in 2022, only 52.2% of infants in Indonesia receive exclusive breastfeeding, below the target of 80%. Previous research shows that the consumption of food bars made from a combination of torbangun and katuk leaf flour can increase breast milk production, compared to consuming the leaves separately. Additionally, maternal nutritional status also plays a role. Mothers with good nutritional status tend to produce breast milk of better quantity and quality. Objectives: This study aimed to evaluate and compare the effectiveness of food bars made from katuk and torbangun leaf flour in increasing breast milk production and the nutritional status of breastfeeding mothers in Limo Subdistrict, Depok. Methods: This study employed a quasi-experimental method with a pre- and post-test without control group design. This study was conducted for four days. Data were analyzed using the Shapiro-Wilk test for normality, followed by appropriate statistical tests (paired t-test if normally distributed or Wilcoxon test if non-normally distributed). The sample consisted of 15 participants selected through simple random sampling. Results: The paired t-test results showed a p-value of <0.001, indicating a significant difference in breast milk production before and after the consumption of food bars made from katuk and torbangun leaf flour. However, the analysis of maternal nutritional status yielded a p-value of 0.317 (>0.05), indicating no significant difference in maternal nutritional status before and after the consumption of the food bars. Conclusions: The findings indicate that consuming food bars made from katuk and torbangun leaf flour effectively increases breast milk production. However, their consumption does not significantly affect the nutritional status of breastfeeding mothers.